Influence of cocoa butter extraction by leaching and hydraulic pressing on the lipid profile characterized by chromatography and vibrational spectroscopy - Palacios Hilario, Antony Yourgen (2023)
Cocoa butter is widely used in the food field, especially in the production of chocolates, so it is obtained mainly by pressing and solvent methods. The present research work was aimed at comparing both extraction methods in order to determine the qualitative and quantitative effect on the fatty acid profile. The qualitative results obtained by mid-infrared spectroscopy (MIR) indicated similar presence of functional group vibrations throughout the wavelength range studied. At the quantitative level, gas chromatography indicated that the major fatty acids (palmitic, stearic and oleic) did not present significant differences (p<0.05). The use of hydraulic pressing is a much more environmentally friendly method, although its great disadvantage was found in the extraction yield.